Implementasi Perlindungan Hukum Terhadap Anak Yang Menjadi Korban Kekerasan Seksual Di Kabupten Lombok Barat - Abdul Hamid; Laely Wulandari; Idi Amin; Titin Nurfatlah (Private Law, 2022)
This research was conducted with the aim of knowing the implementation of legal protection for children as victims of sexual violence in West Lombok Regency. This research is empirical legal research with approach methods, namely the statutory approach, conceptual approach and sociological approach. Sources of data are from library data and field data. The types of data are primary data and secondary data. Data collection techniques are by means of document studies and field studies in the form of interviews. Data analysis with descriptive quantitative analysis. The result of the research is that the implementation of protection for children who are victims of sexual violence in West Lombok Regency is in accordance with what is mandated in the Child Protection Act. As for the obstacles in the implementation of legal protection for children who are victims of sexual violence in West Lombok Regency, among others, the lack of parental supervision from both the victim and the perpetrator, the social environment including the family environment, limited child psychologists, especially in mentoring whose parties involve children who are still young. very small, remote place of residence and in West Lombok Police itself there is no Special Room for Children (RKP).